2020
DOI: 10.3390/nu12123603
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Caffeine Intake on the Fat Oxidation Rate during Exercise: A Systematic Review and Meta-Analysis

Abstract: A number of previous investigations have been designed to determine the effect of acute caffeine intake on the rate of fat oxidation during exercise. However, these investigations have shown contradictory results due to the differences in the exercise protocols used or the co-ingestion of caffeine with other substances. Hence, to date, there is no consensus about the effect of caffeine on fat oxidation during exercise. The purpose of this study was to conduct a systematic review followed by a meta-analysis to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 68 publications
4
30
2
Order By: Relevance
“…Caffeine is sufficiently hydrophobic to pass through all biological membranes and is readily distributed throughout all tissues of the body [ 7 ]. Increased muscle oxygen saturation [ 11 ], improved function of the Na + /K + pump [ 12 ], enhanced calcium ion release from the sarcoplasmic reticulum [ 13 ] and increased fatty acid mobilization and fat oxidation [ 14 ] have been proposed as contributors for increased performance after oral caffeine intake. Interestingly, these mechanisms are mainly effective during endurance-based activities as caffeine has an amplified ergogenic effect on more oxidative fibre types [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine is sufficiently hydrophobic to pass through all biological membranes and is readily distributed throughout all tissues of the body [ 7 ]. Increased muscle oxygen saturation [ 11 ], improved function of the Na + /K + pump [ 12 ], enhanced calcium ion release from the sarcoplasmic reticulum [ 13 ] and increased fatty acid mobilization and fat oxidation [ 14 ] have been proposed as contributors for increased performance after oral caffeine intake. Interestingly, these mechanisms are mainly effective during endurance-based activities as caffeine has an amplified ergogenic effect on more oxidative fibre types [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is probable that the placebo effect of caffeine on fat oxidation during exercise is lower or even inexistent in habitual caffeine consumers, as has been recently found for muscle performance [17]. Third, a recent meta-analysis indicated that the ability of caffeine to increase fat oxidation during exercise is higher in doses ≥ 6 mg/kg when compared to~3 mg/kg [6]. Future investigations should determine if the expectancy of having received a dose of 6 mg/kg of caffeine also produces a higher effect on fat oxidation during exercise than the expectancy of receiving 3 mg/kg.…”
Section: Discussionmentioning
confidence: 98%
“…For this reason, caffeine is broadly consumed before exercise in doses from 3 to 9 mg per kg of body mass [4] (i.e., mg/kg) in the form of coffee or tea (natural sources) or in capsules/pills, pre-workout supplements, energy drinks, and caffeinated gums (artificial sources) [5]. Although less-well studied, acute caffeine intake can also produce a shifting in substrate oxidation during exercise when ingested in doses similar to the ones used for performance enhancement [6,7]. Briefly, pre-exercise ingestion of caffeine has the capacity to increase fat oxidation rate during incremental [8] and steady-state exercise [9] while it concomitantly reduces carbohydrate utilization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of caffeine to increase fat utilization during exercise may be an attractive effect for those individuals enrolled in exercise programs seeking body weight reduction and fat mass loss. The higher fat oxidation rate during exercise found after caffeine intake [4][5][6][7] may aid to produce a faster reduction of fat mass, as caffeine induces a higher amount of fat oxidized per exercise session [5]. However, this substance should be ingested chronically before the exercise sessions of a weight loss program to produce measurable changes in body composition as caffeine increases fat utilization in the range of 0.08 to 0.14 g/min -equivalent to 4.8-8.4 g of "extra" fat utilized per exercise session of 60 min of duration- [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%